What AI Tools Assist with Elderly Care? A Comprehensive Review of Digital Health Solutions - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The global demographic shift toward an aging population presents a significant challenge to traditional healthcare systems, increasing the demand for sustain...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics